1967
DOI: 10.1128/jb.93.1.142-150.1967
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Multiple Molecular Forms of Yeast β-Glucosidase in a Hybrid Yeast

Abstract: A mixture of f3-glucosidases from Saccharomyces fragilis (Y-18) and S. dobzhanskii (Y-19) eluted from diethylaminoethyl cellulose in two peaks, whereas the enzyme from a hybrid, S. fragilis x S. dobzhanskii (Y-42), eluted in a single broad peak. The highest Y-42 activity fractions eluted at a sodium chloride molarity which was intermediate to the molarities at which most of the Y-18 and Y-19 activity was eluted. In cellulose polyacetate strips, Y-42 enzyme migrated as a diffuse band which spanned the distances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1967
1967
1991
1991

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…However, the molecular weight of bacterial ,8-glucosidase is one-half to one-third that of yeast j8-glucosidase. Fleming and Duerksen (8) postulated that the yeast 13-glucosidase is composed of three or four structural subunits and calculated the molecular weight of the polymer and monomer as 325,000 and 110,000, respectively. Thus, it appears that the bacterial f3-glucosidase has a size similar to that of one subunit of yeast f3-glucosidase.…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular weight of bacterial ,8-glucosidase is one-half to one-third that of yeast j8-glucosidase. Fleming and Duerksen (8) postulated that the yeast 13-glucosidase is composed of three or four structural subunits and calculated the molecular weight of the polymer and monomer as 325,000 and 110,000, respectively. Thus, it appears that the bacterial f3-glucosidase has a size similar to that of one subunit of yeast f3-glucosidase.…”
Section: Discussionmentioning
confidence: 99%
“…We referred earlier to the fact that similar characteristics were displayed by the yeast ,B-glucosidases throughout most of the purification procedure. An exception was that Y-19 enzyme eluted from columns of DEAE cellulose at an applied salt concentration of 0.215 M, whereas Y-18 enzyme eluted at 0.230 (4). Perhaps the most decisive difference between the Y-18 and Y-19 enzymes is their serological specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The enzymes appeared to be characteristic of those obtained from the parent yeast strains. Additional studies, however, suggested that the hydrolytic activity against 13-glucosides in the hybrid yeast might actually result from a population of hybrid molecules with varying compositions of two distinct polypeptides (4). If such were the case, mechanisms which regulate the synthesis of these hybrid enzymes would be unique among the variety of control mechanisms known to exist for other carbohydrase systems in yeasts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Y-14 was originally isolated by Wickerham and Burton (6). Y-1057 A l Presented in part at the annual meeting of the American Society for Microbiology, Los Angeles, Calif., [1][2][3][4][5] May 1966. The material in this paper is part of a thesis submitted by the senior author to the Graduate School of the University of Kansas in partial fulfillment of the requirements for the Ph.D.…”
Section: Methodsmentioning
confidence: 99%